Comprehensive Evaluation of Power Grid Security and Benefit Based on BWM Entropy Weight TOPSIS Method. Issue 1 (December 2020) - Zhao, Lang; Li, Hui; Wang, Zhidong; Peng, Dong; Xue, Yawei; Ai, Xin
Abstract: With the gradual integration of various forms of energy, the energy utilization rate has increased and it also brings great challenges to grid evaluation. Therefore, the use of scientific and reasonable comprehensive evaluation method can provide effective help for the development of power grid. In order to solve the problem that the traditional single evaluation method is used in the comprehensive evaluation of power grid, resulting in too strong subjective awareness and lack of evaluation of the objective original data itself and uneven weight distribution, this paper proposes that Nash equilibrium solution is introduced into BWM entropy weight as the goal of coordination and optimization. In the method, the comprehensive weight is calculated, and the distance between the selected scheme and the ideal scheme is sorted by TOPSIS. This method combines all the information of objective data to balance the subjective and objective weight. Through this method, 16 indicators of safety and benefit in 25 provinces in 2017 of State Grid Economic Research Institute are analyzed, and the feasibility of this method is verified.